6(x+8)=3(x+1)

Simple and best practice solution for 6(x+8)=3(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+8)=3(x+1) equation:



6(x+8)=3(x+1)
We move all terms to the left:
6(x+8)-(3(x+1))=0
We multiply parentheses
6x-(3(x+1))+48=0
We calculate terms in parentheses: -(3(x+1)), so:
3(x+1)
We multiply parentheses
3x+3
Back to the equation:
-(3x+3)
We get rid of parentheses
6x-3x-3+48=0
We add all the numbers together, and all the variables
3x+45=0
We move all terms containing x to the left, all other terms to the right
3x=-45
x=-45/3
x=-15

See similar equations:

| 18-9p=-10p | | (230+1)+p=1265 | | 8x-32=-6x-96 | | 3p-8=6+p | | 5x=8.3 | | 4=8+m | | 7=x-5+2x | | -3m-10=8m+1 | | 14d=13d+6 | | 52+4-w=9w-w(w-) | | 16=5m-4 | | 3(2x-1)-2(2x+4)=11x | | -3(1+8n)=-27 | | T=7.5n+5 | | d/20+1080+d/16=1260 | | -62=r+-10 | | X+x+50+20=180 | | 198-x=75 | | 11y/14-8=6-2y/7 | | 7+5c=-9+6c | | 0.09x=0.9 | | 5(2x+3)=6x+7 | | (15+2x)(9+2x)-15*9=112 | | 99=3r | | 3n-8n=-5 | | 6(−3x+8)=−6(8x−8) | | -7+p/9=9 | | 40=2t | | x^-5x-84=20 | | 0.15(y​-0.2)=2-​0.5(1​-y) | | F(x)=5(x-5)+17 | | 3(×-27)=12x |

Equations solver categories